Quantifying segregation on a small scale: how and where locality determines student compositions and outcomes taking Hamburg, Germany, as an example. Issue 3 (2nd July 2020) - Leist, Sebastian A.; Perry, Laura B.
ABSTRACT: Increased social and academic segregation are known side effects of school choice policies in market-driven environments that facilitate competition amongst schools. Aiming at complementing foundational knowledge in quantifying segregation, this study first defines school markets (i.e., geographical context) based on student transitions from primary school to secondary school in Hamburg, Germany. Second, genuine spatial measures of segregation are applied to generate differentiated in-situ insights. In general, social segregation appears evident between school markets, school types, and individual schools and, thus, shapes social compositions of secondary schools. The pattern of student transfers across the city confirms that parents are selecting particular schools for their children, resulting in different schools servicing different composition of students and so markets. Furthermore, the findings suggest that school markets in both very affluent and very deprived areas are spatially isolated and hence persistently reproduce wealth and affluence as well as poverty and disadvantage.